الطرق التجارية في مملكة الأنباط - al-Dalaeen, Marwan Atef (Journal of Al-Tamaddun, 2010)
Recent archaeological discoveries have enriched our knowledge of Nabataean trade routes and caravans? stations. The geographic and strategic of the area have been influential factors in determining the trade routes' positions. The routes were provided with watching towers, and rest houses in order to protect and facilitate caravans. The occasion scarcity of the archaeological evidence makes it blur to distinguish between local and regional trade routes and furthermore it is uncertain whether some routes were in use. Nabataean economic interests were not restricted to land trade, whereas they also used sea to transport their goods. They had their own boats that they developed into ships that would navigate in the Red Sea and the Mediterranean. Nabataean profited from imposing levies on caravans passing thorough Nabataea under their protection.